PENGARUH LATAR BELAKANG PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BERKAH CIPTA PERSADA BEKASI JAWA BARAT - Septyansya Siwi Arumaningtyas; Agung Tri Putranto (Jurnal Menara, 2024)
The purpose of this study was to determine the effect of educational background and work experience on employee performance at PT. Berkah Cipta Persada in Bekasi, partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 93 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are educational background has a significant effect on employee performance with a coefficient of determination of 41.0% and hypothesis testing is obtained t arithmetic > t table or (7.957 > 1.986). Work experience has a significant effect on employee performance with a coefficient of determination of 50.5% and hypothesis testing is obtained t count > t table or (9,641 > 1,986). Educational background and work experience simultaneously have a significant effect on employee performance with the regression equation Y = 9.919 + 0.259X1 + 0.502X2. The value of the coefficient of determination is 55.1% while the remaining 44.9% is influenced by other factors. Hypothesis test obtained value of F arithmetic > F table or (55,132 > 2,710).